SILICA IODIDE CATALYZED ULTRASOUND ASSISTED ONE-POT THREE-COMPONENT SYNTHESIS OF 3,4-DIHYDROPYRIMIDINE-2-(1H)-ONES/-THIONES - Khanum, Amreen; Khan, Riyaz-ur-Rahaman; M, Mangalavathi; Pasha, Mohamed Afzal (Universal Journal of Pharmaceutical Research, 2021)
Aim and objective: A single-pot three-component reaction for a competent preparation of biologically active 3,4-dihydropyrimidineones/-thiones using Silica Iodide (SiO2-I) as a reliable and reusable heterogeneous catalyst is developed. Methods: The reaction proceeds via condensation of araldehydes, urea/thiourea, ethyl acetoacetate in ethanol under ultrasonic condition to afford the target molecules in best yields. The reaction proceeds in 30 min and SiO2-I has shown high proficiency in performing this single-pot Biginelli reaction. Results: The use of catalytic SiO2–I (0.1 g) accelerated the reaction and gave the product in excellent yield. Maximum yield of the product was found to be 96% in ethanol Conclusion: Study concludes the used method has shown many advantages, mild condition, short duration, simple isolation and best yields of products. Peer Review History: Received: 1 August 2021; Revised: 9 September; Accepted: 10 October; Available online: 15 November 2021 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia. Reviewers: Dr. Neelam H. Zaidi, Fiji National University, Fiji, drneelamzaidi@gmail.com Dr. U. S. Mahadeva Rao, Universiti Sultan Zainal Abidin, Terengganu Malaysia, raousm@gmail.com Dr. Hayriye Eda Şatana Kara, Gazi University, Turkey, eda@gazi.edu.tr Dr. Andrzej Szymański, Poznan University of Technology, Poland, andrzej.szymanski@put.poznan.pl